"Effect of the linking unit on the calamitic-shaped liquid crystal: a comparative study of two homologous series of benzoate and cinnamate linked compounds". (4th March 2019) - Kashyap, Dinesh; Patel, Sunil; Prajapat, Varsha; Sharma, Vinay; Vasava, Dilip
Abstract: Two homologous series based on three linking groups have been synthesized and well characterized by elemental analyses and spectroscopic techniques such as Fourier transform infrared [FT-IR] and proton magnetic resonance magnetic resonance [ 1 H NMR] spectroscopy. The mesomorphic properties of these compounds were observed by using optical polarized microscopy (POM) and confirmed by differential scanning calorimetry (DSC) analysis. In this present investigation, we have synthesized two homologous series viz. ( E )-4-(3-(4-(tetra decanoyloxy) phenyl) acryloyl) phenyl-4-n-alkoxy benzoate (Series-1) and 4-(( E )-3-(4-((( E )-3-(4-n-alkoxy phenyl) acryloyl) oxy) phenyl)-3-oxo prop-1-en-1-yl) phenyl tetradecanoate (Series-2). Both of the series are differing with respect to the first linking group. All the homologous in following series displays LC properties on heating as well as cooling condition except first four homologous (C1 to C4 ) in series-1 and six homologous (C1 to C6 ) in series-2. To get more insights, the HOMO, LUMO studies are carried out which supports intramolecular charge transfer interactions in this class of mesogens. Graphical Abstract: